Child development, physiological stress and survival expectancy in prehistoric fisher-hunter-gatherers from the Jabuticabeira II shell mound, South Coast of Brazil - Pezo-Lanfranco, Luis (PLoS One, 2020)
In this study, we shed light on the interdependency of child growth, morbidity and life expectancy in the fisher-hunter-gatherers of the Jabuticabeira II shell mound (1214–830 cal B.C.E. - 118–413 cal C.E.) located at the South Coast of Brazil. We test the underlying causes of heterogeneity in frailty and selective mortality in a population that inhabits a plentiful environment in sedentary settlements. We reconstruct osteobiographies of 41 individuals (23 adults and 18 subadults) using 8 variables, including age-at-death, stature, non-specific stress markers (cribra orbitalia, porotic hyperostosis, periosteal reactions, periapical lesions and linear enamel hypoplasia), as well as weaning patterns based on stable isotope data to examine how stress factors module growth and survival. Our results show that shorter adult statures were linked to higher morbidity around weaning age and higher chances of dying earlier (before 35 years) than taller adult statures. In addition, short juvenile stature was related to physiological stressors and mortality. The adult “survivors” experienced recurrent periods of morbidity during childhood and adulthood, possibly associated with the high parasite load of the ecosystem and dense settlement rather than to malnourishment. An association between early-stress exposure and premature death was not demonstrated in our sample. To explain our data, we propose a new model called “intermittent stress of low lethality”. According to this model, individuals are exposed to recurrent stress during the juvenile and adult stages of life, and, nevertheless survive until reproductive age or later with relative success.